Perspectives on adaptation in natural and artificial systems - Booker, Lashon (Proceedings volume in the Santa Fe Institute studies in the sciences of complexity., 2005)
Introduction: Adaptation, Evolution, and Intelligence, Lashon Booker, Stephanie Forrest, Melanie Mitchell, and Rick Riolo PART 1: GENETIC ALGOROTHMS AND BEYOND 1. Genetic Algorithms: A 30 Year Perspective, Kenneth DeJong 2. Human-Competitive Machine Intelligence by Means of Genetic Algorithms, John R. Koza 3. John Holland, Facetwise models, and Economy of Thought, David E. Goldberg PART 2: COMPUTATION, ARTIFICIAL INTELLIGENCE, AND BEYOND 4. An Early Graduate Program in Computers and Communications, Arthur W. Burks 5. Had We But World Enough and Time, Oliver G. Selfridge 6. Discrete Event Abstraction: An Emerging Paradigm for Modeling Complex Adaptive Systems, Bernard P. Zeigler 7. Good Old-Fashioned AI and Genetic Algorithms: An Exercise in Translation Scholarship, Herbert A. Simon 8. Moore's Law, Artificial Evolutionm and the Fate of Humanity, Douglad R. Hofstadter PART 3: THE NATURAL WORLD AND BEYOND 9. Evolution of Complexity in Microbial Populations, Julian Adams 10. Favored Places in the Selfish Herd: Trading Off Food and Security, Bobbi S. Low, Doug Finkbeiner, and Carl Simon 11. Tags, Interaction Patterns and the Evolution of Cooperation, Rick Riolo, Robert Axelrod, and Michael D. Cohen 12. The Impact of Environmental Dynamics on Cultural Emergence, Robert G. Reynolds and Salah Saleem 13. John Holland and the Evolution of Economics, Kenneth J. Arrow 14. Cognition: The Black Box of Economics, W. Brian Arthur Index.